Hergé dans la théorie des sphères: Problématique de l’insulation et de l’animalité de l’homme dans les aventures de Tintin - Álvares, Cristina (2020)
This paper aims at reading Hergé’s major work in the light of Sloterdijk’s theory of spheres and Agamben’s reflexions on adventure in order to examine the place and function of the island in the adventures of Tintin, a hero without insulation. Much attention is given to the boundery topology of adventure in our discussion of the ontological transitions (human, animal) taking place on the threshold between in and out and of their anthropogenetic significance. We defend that every adventure story is a variation on the anthropogenetic one, and that Hergé and Sloterdijk diverge on the matter of island and insulation.